Tracing Neanderthal mobility through the Romanian Carpathians: A GIS-based least-cost connectivity model - Murătoreanu, George; Cosac, Marian (PLOS ONE, 2025)
Out of the 12,300 known caves within the Romanian Carpathian and Dobrudja mountain area, only 16 have been the focus of consistent archaeological researches which revealed traces of human activity (lithic artefacts, faunal material, combustion areas), roughly consistent with a Middle Palaeolithic technological and/or chronological background. Establishing natural areas connected in terms of accessibility to these caves may offer a different perspective for future researches and, above all, may increase the chances of discovering new caves with traces of human activity. The present study aims to integrate advanced spatial analysis methods, such as Linkage Mapper and Circuitscape, to assess the potential connectivity of these sites. The two models were developed by researchers in the field of biology and belong to the field of deterministic spatial modeling and algorithm-based geospatial analysis. Following the application of these models, we identified the areas of influence of the 16 caves, determined the least-cost paths between them and the main natural obstacles, in order to model spatial connectivity and identify new possible sites along these routes.